CORRELATON OF EMPLOYEE CHARACTERISTICS, HOUSEKEEPING, AVAILABILITY AND USE OF PERSONAL PROTECTIVE EQUIPMENT TOWARDS MINOR INJURY (Study of Apartment X Construction Project, Semarang City) - Muhammad Ghulam Khaqiiqudin; Ida Wahyuni; Bina Kurniawan (Jurnal Kesehatan Masyarakat, 2019)
Minor injury is a minor accident experienced by workers that causes injury but did not cause a loss of 2x24 hours of work hours and can be immediately handled. Neglected minor injury can risk even more severe accidents for workers. The purpose of this study was to analyze the correlation between worker characteristics (age, years of service, level of education and work attitude), housekeeping, the availability of PPE and the use of PPE with the incident of minor injury to workers in Apartment X construction project, Semarang. This type of research was observational analytic research using a cross-sectional study.The population in this study were 144 construction workers of the Apartment X construction project and the sample in this study were 60 workers from the population. The instruments of this study were questionnaires and observation sheets. Statistical data analysis using chi-square test. The results showed that there was a correlation between age (sig 0.002), working period (sig 0.030), attitude (sig 0.0001), housekeeping (sig 0.002) and use of PPE (sig 0.006) with minor injury. There is no correlation between education level (sig 0.120) and the availability of PPE (sig 0.748) with the incidence of minor injury. There were 58.3% of workers have experienced minor injury for the past 6 months. To reduce the incidence of minor injuries to workers, management should always improve the quality of workers by conducting training for workers, optimizing safety talk and safety inspection.